Gaya Komunikasi Melalui Fear of Missing Out (Fomo) dalam Penggunaan Barang Branded Mahasiswa Universitas Muhammadiyah Sumatera Utara - Aldy Zakiani Lubis; Dewi Kurniawati; Emilia Ramadhani (KOLONI, 2026)
This study aims to analyze the experience of Fear of Missing Out (FoMO), students’ communication practices in discussing and responding to the use of branded goods, and the communication styles formed in social interactions within peer groups at Muhammadiyah University of North Sumatra. This research employed a qualitative method with a phenomenological approach. Data were collected through non-participant observation and semi-structured in-depth interviews with students selected through snowball sampling, supported by source triangulation from psychology. Data analysis was conducted through data reduction, data display, conclusion drawing, and verification. The findings show that FoMO in the use of branded goods does not merely appear as a desire to purchase or own similar products, but is more strongly understood as a need to remain informed, follow, and participate in group conversations. Branded goods function as communication symbols that trigger questions, comments, information exchange, and self-adjustment within peer relationships. The findings reveal tendencies toward The Dynamic Style, The Equalitarian Style, and The Relinquishing Style. This study concludes that FoMO is not merely a psychological or consumptive phenomenon, but a communication experience that shapes how students maintain social connectedness and a sense of belonging.